Successful endovascular therapy for an adolescent patient with cerebral venous sinus thrombosis: A case report. Issue 35 (3rd September 2021) - Peng, Tao; Zhang, Zini; Zu, Bifeng; Dan, Bitang
Abstract: Rationale: Cerebral venous sinus thrombosis associated with protein S deficiency is rare in adolescent patients and has high disability and fatality. Patient concerns: A 15-year-old male student presented in the hospital with sudden headache, nausea, and vomiting and was diagnosed with protein S deficiency by gene testing. Diagnoses: Cerebral venous sinus thrombosis due to protein S deficiency was diagnosed in this adolescent patient, who underwent successful endovascular therapy (EVT). Interventions: The patient was treated with standard anti-coagulation therapy including low-molecular-weight heparin (90 IU/kg/Q12 h) and dehydrant (mannitol 125 mL Q8 h); however, the symptoms were not alleviated. Successful EVT was implemented. Outcomes: Both the superior sagittal sinus and bilateral transverse sinus were recanalized after thrombus clearance. The patient achieved a complete recovery without any other stroke recurrence during follow-up. Lessons: EVT can be performed with favorable and effective clinical outcomes in adolescent cerebral venous sinus thrombosis patients with protein S deficiency. EVT associated with standard anti-coagulation therapy may improve the prognosis and reduce mortality among such patients.